2012
DOI: 10.1259/bjr/21182091
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical characteristics and imaging findings of acute cholangitis with and without biliary dilatation

Abstract: Acute cholangitis can present without biliary dilatation on imaging, and the most common causes are CBD stones and sludge. The patients with acute cholangitis without biliary dilatation have different clinical characteristics and imaging findings compared with those with acute cholangitis presenting with biliary dilatation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Although methods for the direct imaging of AC have yet to be established, research suggests that transient hyperattenuation differences (THAD) in the hepatic parenchyma on early‐phase of dynamic CT as well as transient heterogeneous enhancement in the hepatic parenchyma on early‐phase of dynamic MRI may provide a specific imaging finding for AC . Other recent studies have also suggested that THAD may be useful for severity grading .…”
Section: Diagnostic Criteria For Acute Cholangitismentioning
confidence: 99%
“…Although methods for the direct imaging of AC have yet to be established, research suggests that transient hyperattenuation differences (THAD) in the hepatic parenchyma on early‐phase of dynamic CT as well as transient heterogeneous enhancement in the hepatic parenchyma on early‐phase of dynamic MRI may provide a specific imaging finding for AC . Other recent studies have also suggested that THAD may be useful for severity grading .…”
Section: Diagnostic Criteria For Acute Cholangitismentioning
confidence: 99%
“…However, (19) demonstrated that acute cholangitis without CBD dilatation is caused by CBD stones and sludge, with the latter also being implicated in the development of acute cholangitis (20). Interestingly, in one CBDdil(-) patient included in the present study, secretions of bile and sludge from the Ampulla of Vater were observed, indicating that sludge may be present during CBD without CBD dilatation.…”
Section: Discussionmentioning
confidence: 54%
“…THAD is a compensatory reaction to the decreased portal flow associated with hepatic pathologies [25,26]. Several studies have investigated the correlation between the degree of THAD and markers of inflammation such as C-reactive protein, leukocyte count, and the severity of acute cholecystitis, but have found discordant results [26][27][28][29]. Our study showed increased stiffness of the GB bed of the liver in acute cholecystitis, suggesting that only hyperemic changes, not necroinflammation, are associated with THAD.…”
Section: Discussionmentioning
confidence: 62%